Peran Motivasi Hedonis Memediasi Pengaruh Sifat Materialisme Terhadap Perilaku Pembelian Impulsif Secara Online - Prawira Laksana, Kadek Andika; Suparna, Gede (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the influence between of materialism to online impulsive buying behavior with hedonic motivation as mediation variable. The data in this study, using path analysis to discuss how the direct influence of materialism on the hedonic motivation and materialism and hedonic motivation on impulsive buying behavior online, This study also accompanied Sobel test to determine the effect of indirect to know how the role of hedonic motivation in mediating. The sample size used was 120 people with a survey method using a questionnaire that measured with Likert scale. Based on the results path analysis found that the variable materialism significantly affects the hedonic motivation, and the variable materialism and hedonic motivation significantly effect on impulsive buying behavior online. Sobel test results showed that the hedonic motivation variables is able to mediate the effect of the materialism on impulsive buying behavior online. This study showed no plans on buying behavior of online shopping activity in Indonesia, which is influenced by the emotional nature of consumer owned.
Keywords: internet, online impulsive buying behavior, materialism, hedonic motivation